Differences in alcohol cognitions, consumption, and consequences among first-time DUI offenders who co-use alcohol and marijuana. (1st October 2018) - Smart, Rosanna; Osilla, Karen Chan; Jonsson, Lisa; Paddock, Susan M.
Highlights: Alcohol and marijuana co-use is common among first-time driving under the influence (DUI) offenders. Co-users exhibit greater severity in drinking quantity than alcohol-only users. Lower abstinence self-efficacy contributes to risky profile of co-users. Co-users may benefit from programs that target self-efficacy and negative affect. Methods to screen and identify co-use at DUI program intake should be considered. Abstract: Background: A significant portion of alcohol-related DUI offenders engage in co-use of alcohol and marijuana (AM). Given expanding marijuana legalization and the impaired driving risks associated with co-use, it is of increased importance to understand how characteristics of AM co-users compare to those who use alcohol only (AO) in order to inform DUI interventions and prevent recidivism. Methods: Participants were 277 first-time DUI offenders enrolled in a first-time DUI offender program across three locations. Using well-established measures, we evaluated differences in alcohol-related cognitions (positive expectancies and self-efficacy), frequency and quantity of alcohol consumption, and alcohol-related consequences between AO users and AM co-users by running a series of multivariate generalized linear models. Results: Compared to AO users, AM co-users reported lower self-efficacy to achieve abstinence and avoid DUI. Differences in abstinence self-efficacy largely explain higher relative rates of average and peak drinking quantity and higher odds of binge drinking among AM co-user. Despite lower self-efficacy and higher drinking quantity, there were no significant differences between AM and AO-users on alcohol-related consequences and past month reports of drinking and driving. Conclusions: Our results provide preliminary evidence that DUI offenders who co-use alcohol and marijuana have higher alcohol use and lower self-efficacy than AO-users, and long-term consequences for this group should be monitored in future research. DUI programs may screen and identify co-users and consider tailoring their interventions to build self-efficacy to address the risks associated with AM co-use uniquely.